2012
DOI: 10.1002/ijc.27824
|View full text |Cite
|
Sign up to set email alerts
|

The severity of duodeno‐esophageal reflux influences the development of different histological types of esophageal cancer in a rat model

Abstract: The mechanism through which each histological type of carcinoma arises from the esophageal mucosa remains unknown. This study was designed to investigate whether there is an association between the severity of duodeno-esophageal reflux and the histological type of esophageal cancer. A series of 120 male Fischer rats, weighing~180 g, were randomized to receive one of the following procedures: duodeno-forestomach reflux (DFR) with reduced exposure to duodenal contents, duodeno-esophageal reflux (DER) with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The superficial part between the epithelial border and the proliferating work creates certain protection against the carcinogens entering from the gastric lumen into the mucosa. Mucous erosion in the antrum, probably represent an increased risk of carcinogenesis, by increasing the probability of cell proliferation and by reducing the density of the mucosa above the proliferative portion 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The superficial part between the epithelial border and the proliferating work creates certain protection against the carcinogens entering from the gastric lumen into the mucosa. Mucous erosion in the antrum, probably represent an increased risk of carcinogenesis, by increasing the probability of cell proliferation and by reducing the density of the mucosa above the proliferative portion 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In brief, high exposure to duodenal contents promotes the development of EADC, and low exposure induces ESCC. The severity of the duodenoesophageal reflux in rodents is associated with the development of different histological types of esophageal carcinoma (11). In the present study, ESCC was shown to arise from dysplastic changes to squamous cells that were naturally located proximal to the columnar-lined epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The rat model demonstrated the histopathological sequence of events from GERD to EADC as an inflammation-metaplasia-dysplasia-adenocarcinoma (ADC) sequence. Furthermore, a recent study has established a correlation between the quantity of reflux and the likelihood of developing EADC and ESCC (11). …”
Section: Introductionmentioning
confidence: 99%
“…After fasting for 24 h, a midline laparotomy incision was made under inhalation anesthesia. Reflux of duodenal contents was induced according to previously reported procedures (Figure ).…”
Section: Methodsmentioning
confidence: 99%